DESCRIPTION OF THE QUALITY OF LIFE OF POOR HOUSEHOLDS BENEFICLARIES FAMILY HOPE PROGRAM IN MEURAXA SUBDISTRICT, BANDA ACEH - Fadli Syahputra (Jukema (Jurnal Kesehatan Masyarakat Aceh), 2021)
Background: The lack of PKH Beneficiary Families (KPM) who participated in the health examination of pregnant women and toddlers as well as the lack of optimal implementation of education, and still low healthy lifestyle among the community tha causes vulnerable to various diseases, the ability of the community to carrying out daily activities, as well as the ease of access to information, etc. are some factors that affect the level of quality of life of PKH beneficiaries. This study aims to determine factors related to the quality of life of poor families of PKH beneficiaries. Methods: This research is a descriptive study with a cross-sectional design. The sample in the study was 73 respondents in KPM PKH in Meuraxa Subdistrict, Banda Aceh. Analyze data using univariate and Likert scales. Result: Research shows that respondents were predominantly primary education (72.6%), unemployed (58.9%), moderate income (52.1%), number of extended family members (68.5%), long receiving PKH benefits for 3 years (41.1%), ownership of small family assets (60.3%), and respondents with poor quality of life (58.9%). The domain image of physical health quality almost half had a good quality of life (47.6%), psychological domain mostly had a good quality of life (54.1%), the domain of social relations had half good quality of life (50.1%), and the environmental domains almost half have a good quality of life (46.2%). Recommendation: The government needs to intensify the family planning program, so that every household beneficiary of PKH can plan their household better, as well as conduct training and capital loan for small businesses in housewives that can later help the family economy so as to improve the quality of life of the beneficiaries poor of PKH.